Case Report: Surgical timing for Blount’s disease: a case report and systematic review - Wang, Bing; Miao, Zukang; Yu, Xiuchun; Zhou, Ke; Liu, Ning; Zhai, Kai; Zheng, Shu; Sun, Haining (Frontiers in Endocrinology, 2025)
BackgroundCurrently, Blount’s disease is treated in a variety of ways, but the optimal timing of treatment and the choice of optimal treatment regimen have yet to be determined. We report a case of a patient who failed multiple surgical treatments and underwent 3D-printed osteotomy guide-assisted proximal tibial orthopedic external fixation in adulthood to restore normal lower limb mechanical axis and suggest optimal treatment modalities in light of the systematic literature.MethodsA case of Blount’s disease patient who was misdiagnosed and missed and underwent multiple surgical treatments was retrospectively studied. According to the PRISMA statement, a systematic review of electronic databases such as PubMed, Embase, and Web of Science was conducted to explore the optimal timing of surgery for Blount’s disease from 2010.ResultsA boy born in 2001 was found to have a varus deformity in his left knee joint at the age of 2 years, which was not diagnosed. At the age of 7 years, he was diagnosed with Blount’s disease and underwent multiple surgeries over the following years, all of which resulted in recurrences. At the age of 21 years, he underwent high osteotomy and external fixation of the proximal left tibia using a 3D-printed guide plate in our hospital. At present, the external fixation has been taken out, and the lower limb force line has recovered well. The timing and choice of treatment for Blount’s disease are important for the patient’s prognosis. The systematic review analyzed a total of 23 studies with a combined sample size of 679 cases, it provides recommendations for treatment strategies based on patient age.ConclusionThe patient’s age and degree of deformity are key in determining the timing and treatment plan. For patients with early-onset, who are under four years old, they may begin with a conservative treatment strategy, moving to a timely osteotomy if the initial approach proves ineffective. For patients with late-onset, 4-10 years old, there are no recommendations for definitive treatment at this time. Patients over 10 years old should have their bone age and growth potential evaluated, with epiphysiodesis recommended for those with a growth potential greater than 2 years and osteotomy recommended for those with less than 2 years to achieve a complete correction of the deformity.